2014
DOI: 10.1590/s1516-35982014000500004
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of naturally contaminated liquid nitrogen storage tanks

Abstract: -The objective of this study was to evaluate the efficacy of cleaning and decontamination procedures in liquid nitrogen tanks. We evaluated 151 canisters and 133 bottoms from 133 nitrogen tanks of companies or farms for the presence of bacteria and fungi. Samples were collected from the canisters and the bottom of tanks containing liquid nitrogen. Tanks were divided into Group 1 (G1): tanks decontaminated with 2% glutaraldehyde -Glutaron ® II (n = 16 canisters in 8 tanks); Group 2 (G2): decontamination with 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Pessoa et al . [ 43 ] reported that up to 84.3% of farms and 100% of companies in Southern Brazil use LN 2 contaminated with bacteria, fungi, or both. Therefore, an alternative method for cryopreservation that avoids exposing samples directly to LN 2 is required.…”
Section: Discussionmentioning
confidence: 99%
“…Pessoa et al . [ 43 ] reported that up to 84.3% of farms and 100% of companies in Southern Brazil use LN 2 contaminated with bacteria, fungi, or both. Therefore, an alternative method for cryopreservation that avoids exposing samples directly to LN 2 is required.…”
Section: Discussionmentioning
confidence: 99%
“…LN 2 can also serve as an effective storage medium for pathogens (29). Microorganisms that can potentially survive after being cryopreserved by LN 2 include bacteria, fungi, yeasts, and viruses (29,35).…”
Section: Potential Health Outcomes Associated With Biological Contaminationmentioning
confidence: 99%
“…LN 2 can also serve as an effective storage medium for pathogens (29). Microorganisms that can potentially survive after being cryopreserved by LN 2 include bacteria, fungi, yeasts, and viruses (29,35). Examples of microorganisms that have been found in LN 2 tanks used to store biological specimens include Escherichia coli, Bacillus cereus, Mucor spp., Staphylococcus spp., and Pseudomonas aeruginosa, some of which can be spread through unhygienic practices (29).…”
Section: Potential Health Outcomes Associated With Biological Contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several methods for sterilizing tanks that involve ethylene dioxide, alcohols, or glutaraldehyde. [10][11][12] Laboratories should define when tanks will be sterilized and the procedure for sterilizing tanks. Attention should be paid to safety of the tissue and to safety of the staff members performing the sterilization.…”
Section: Ongoing Quality Controlmentioning
confidence: 99%